Injectable and biodegradable piezoelectric hydrogel for osteoarthritis treatment - Vinikoor, Tra; Dzidotor, Godwin K.; Le, Thinh T.; Liu, Yang; Kan, Ho-Man; Barui, Srimanta; Chorsi, Meysam T.; Curry, Eli J.; Reinhardt, Emily; Wang, Hanzhang; Singh, Parbeen; Merriman, Marc A.; et al. (Nature communications, 2023)
Osteoarthritis affects millions of people worldwide but current treatments using analgesics or anti-inflammatory drugs only alleviate symptoms of this disease. Here, we present an injectable, biodegradable piezoelectric hydrogel, made of short electrospun poly-L-lactic acid nanofibers embedded inside a collagen matrix, which can be injected into the joints and self-produce localized electrical cues under ultrasound activation to drive cartilage healing. In vitro, data shows that the piezoelectric hydrogel with ultrasound can enhance cell migration and induce stem cells to secrete TGF-β1, which promotes chondrogenesis. In vivo, the rabbits with osteochondral critical-size defects receiving the ultrasound-activated piezoelectric hydrogel show increased subchondral bone formation, improved hyaline-cartilage structure, and good mechanical properties, close to healthy native cartilage. This piezoelectric hydrogel is not only useful for cartilage healing but also potentially applicable to other tissue regeneration, offering a significant impact on the field of regenerative tissue engineering. The use of biomaterial scaffolds-based cartilage grafts could potentially innovate the Osteoarthritis (OA) treatment, but has been limited by toxicity concerns and invasive surgical procedures. Here, the authors report an injectable and biodegradable piezoelectric hydrogel with ultrasound activation to offer a minimally invasive approach for OA treatment.